ANALISIS PERSEPSI PENGGUNA LAYANAN TRANSPORTASI LRT KOTA PALEMBANG - Siti Anisah; Bambang Utoyo S; Ika Kustiani (Jurnal Tekno Global, 2020)
LRT is a mass transportation mode for light rail that is expected to make the transfer of personal use to mass transportation users to reduce traffic congestion specifically in the city of Palembang. Services and facilities will be one of the supporters in the use of mass transportation. This study aims to analyze the characteristics of LRT users and the level of satisfaction of LRT passengers and to group parameters into 4  quadrants. The sampling technique used by researchers is accidental sampling. Data processing and analysis with Validity Test, Reliability Test, Satisfaction, IPA. The results showed an analysis of the level of satisfaction of the passengers were quite satisfied, with an average level of satisfaction and importance based on Service Quality on physical factors: 4,287 and 4,743, reliability factors: 4,096 and 4,678, responsiveness factors: 4,18 and 4,60, Guarantee factors and empathy factors: 4,400 and 4,860. Priority grouping into 4 quadrants, quadrant I Security officer, quadrant II cleanliness, comfort of seating in the LRT, ease of ups and downs of LRT for persons with disabilities and the availability of facilities for the disabled and facilities for breastfeeding mothers, Quadrant Analysis III LRT waiting time, availability of relevant information with the Arrival and Departure Schedule, how the speed of employees in responding complaints LRT customer problems and how the hospitality and courtesy of officers in serving LRT customers, Quadrant IV how easy access to the LRT station, how accurate the LRT schedule is and how the LRT rates are charged. Keywords: Mode of Transportation, LRT, Services, Palembang.